Behind the Scenes of Inuit Curriculum Development in Nunavut, 2000–2013 - McGregor, Heather E.; McGregor, Catherine A. (Études Inuit Studies, 2016)
In this article we examine the provision of curriculum in Nunavut between 2000 and 2013. During this time the Government of Nunavut established a mandate to ensure all curriculum from Kindergarten through Grade 12 was founded on Inuit Qaujimajatuqangit (IQ) and supported bilingualism. We describe how the Curriculum and School Services Division of the Department of Education undertook to fulfil this responsibility through unique, made-in-Nunavut curriculum development processes and products. We conclude by outlining the opportunities and challenges evident in the work of creating curriculum, teaching resources, and learning materials that centre Inuit knowledges, languages, and contexts. Dans cet article, nous examinons le contenu des programmes scolaires au Nunavut entre 2000 et 2013. Durant cette période, le gouvernement du Nunavut s’était donné pour mandat de s’assurer que tous les programmes, de la maternelle à la douzième année, seraient basés sur l’Inuit Qaujimajatuqangit (IQ) et qu’ils favoriseraient le bilinguisme. Nous décrivons comment la Direction des services des programmes scolaires du Département de l’éducation a entrepris d’assumer ses responsabilités au moyen d’une façon unique d’élaborer les processus et les produits des programmes. Nous concluons en soulignant les opportunités et les difficultés que l’on rencontre dans la création de programmes, de ressources d’enseignement et de matériel d’apprentissage centrés sur les savoirs, les langues et les contextes inuit.